Health professions education theory and applications - Sana, Erlyn A. (University of the Philippines Manila, 2006)
It embodies the many insights that the NTTCHP faculty members have gained as teachers of teachers in the health professions. Although the authors probably conceptualized the book with teaching as the primary activity of the faculty, it has turned out to also address the needs of the faculty researcher and the faculty administrator. The chapters on curriculum making and instructional design are invaluable guides to curriculum committees and to the faculty in general.